Model Contextual Teaching and Learning (CTL) Menggunakan Bantuan Alat Peraga Meteran untuk Meningkatkan Kemampuan Matematika Materi Pengukuran Suatu Benda pada Siswa Kelas III SDN Nganjat Polanharjo Klaten Semester I Tahun Pelajaran 2018/2019 - Nurjiatun, Nurjiatun (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2019)
The purpose of this study was to analyze: (1) The application of CTL using the aid of meter teaching aids in improving the mathematical abilities of an object measurement material in the first semester of SDN Nganjat Polanharjo Klaten academic year 2018/2019; (2) The active learning of children in mathematics learning material measurement of an object through the application of CTL using the aid of meter teaching aids in SDN Nganjat Polanharjo Klaten in the first semester of the school year 2018/2019; (3) Learning outcomes of children through the application of CTL use the help of meter teaching aids to improve the mathematical skills of material for measuring an object in the first semester of SDN Nganjat Polanharjo Klaten 2018/2019 academic year. The research is class action research (PTK) with procedures, namely planning, action, observation and reflection. The object of the study was Class III students in semester I of the 2018/2019 academic year, totaling 15 students. The technique of collecting data uses observation, interviews, document analysis and assignments. The data analysis technique uses descriptive and comparative analysis. The results of the study concluded: (1) The application of CTL using the help of meter teaching aids can help students to understand the mathematical concepts of measuring objects that are in the natural environment; (2) Implementation of learning in mathematical concepts of measurement by applying CTL using the aid of meter teaching aids can increase students' active involvement in the learning process, students look enthusiastic in participating in learning, class atmosphere becomes conducive to learning, and learning resources are not focused on teachers but are focused on students; (3) After the corrective action was taken, in the first cycle the mathematical abilities of children at Nganjat Polanharjo Klaten Elementary School began to increase, because 11 students (73%) scored above the KKM. At the end of the second cycle, the mathematical abilities of the children of Nganjat Polanharjo Klaten Elementary School were getting better because all children (100%) had scored above the KKM. Thus, learning the mathematical concept of measurement by applying CTL using the aid of meter teaching aids is quite effective for improving cognitive abilities of children of SDN Nganjat Polanharjo Klaten.